Anxiety-related gut microbiota alterations in Parkinson’s disease: distinct associations compared to healthy individuals - Sheng-Hsuan Lin; Sheng-Hsuan Lin; Sheng-Hsuan Lin; Sheng-Hsuan Lin; Ru-Jen Lin; Kai-Yu Chan; Kai-Yu Chan; Chia-Ling Chu; Yan-Lin Chen; Shih-Chen Fu (Frontiers in Cellular and Infection Microbiology)
Background and objectivesAnxiety affects 25–49% of Parkinson’s disease (PD) patients, exacerbating non-motor symptoms and significantly reducing quality of life. Growing evidence suggests that gut microbiota plays a role in anxiety, but whether its impact differs between PD and non-PD populations remains unclear. This study explores the heterogeneity of gut microbiota-associated anxiety in PD and non-PD individuals.MethodsParticipants from the NeuroGenetics Research Consortium provided clinical data, including PD status, anxiety status, and stool samples analyzed via 16S rRNA sequencing. After excluding nine participants with missing anxiety data, 322 individuals were included (193 PD, 129 non-PD). We assessed α-diversity, β-diversity, taxonomic composition, and functional pathways to compare microbial differences between anxious and non-anxious individuals within and across PD and non-PD groups.ResultsBeta diversity analysis revealed significant microbial differences between anxious and non-anxious PD patients (p = 0.043 in Bray-Curtis index) but not in the non-PD group. Escherichia-Shigella was significantly enriched in non-anxious PD patients (p = 0.011). Functional pathway analysis identified distinct metabolic alterations associated with anxiety in PD and non-PD individuals. In non-PD participants, anxiety was linked to increased activity in glycosphingolipid biosynthesis, sphingolipid metabolism, other glycan degradation, glycosphingolipid biosynthesis, and glycosaminoglycan degradation. In contrast, PD patients with anxiety exhibited enrichment in indole alkaloid biosynthesis, linoleic acid metabolism, and polyketide sugar unit biosynthesis.ConclusionGut microbiota-associated anxiety differs between PD and non-PD populations, suggesting distinct pathophysiological mechanisms. These findings underscore the potential of microbiome-targeted interventions as novel therapeutic strategies for anxiety in PD patients.